Understanding and Preventing Ideologically Justified Violence in Custodial Settings: The MICO Paradigm - Dean, Christopher (The prison journal, 2023)
Internationally, secure institutions face a range of challenges presented by detainees convicted or suspected of terrorism-related crimes and those interested or involved in groups that support ideologically justify violence (IJV). Currently, there is an apparent absence of a theoretically grounded but operationally focused paradigm (or conceptual lens) for understanding and preventing IJV within such settings. In response, this article presents such a paradigm, to inform and direct the implementation of coherent organizational policies and practices to address this issue. The paradigm, its theoretical basis, its implications for correctional policy and practice, and limitations are outlined and discussed.